The Fundamental Role of Brand Experience in Building Brand Loyalty Behind The Everlasting Success of Taylor Swift - Ayuning Gitafitri, Betari; Kusumawati, Nurrani (Journal of Consumer Studies and Applied Marketing, 2024)
Even after eighteen years, Taylor Swift remains a major figure in the music industry, with her popularity extending to Indonesia. Booming Swiftie activities from karaoke parties, fun walks, to Eras Tour remakes have gained popularity, driven by her viral songs and TikTok trends. Indonesian Swifties eagerly invest time and money in Taylor Swift related events, from local fan gatherings to traveling abroad for her concerts. This research aims to explore how brand experience drives brand loyalty and examines the roles of brand experience, brand personality, brand satisfaction, and brand love in sustaining Taylor Swift's success in Indonesia. Using a judgmental sampling technique, a mixed-method approach was utilized, involving interviews with 11 respondents and surveys with 305 respondents from 16 regions in Indonesia. Coding with NVivo and PLS-SEM with SmartPLS were used to examine the data. The study identified several factors that support Taylor Swift’s ongoing success and exposure, emphasizing Swift’s exceptional brand experience, public persona, ability to comprehend market demand and fan expectations, emotional connection fostered with her fans, and the persistent quality of both her music and performances. The findings also showed that Taylor Swift’s brand loyalty is significantly and positively impacted by brand experience, brand satisfaction, and brand love. Brand experience significantly affects brand loyalty both directly and indirectly through brand personality, brand satisfaction, and brand love as the mediating variables. In addition, perceived quality is found to have a significant positive impact on brand satisfaction, and brand satisfaction has a significant positive impact on brand trust. These results provide artists and record labels in the music industry with valuable insights to improve their brand management strategy and enhance brand loyalty, therefore extending the artists’ longevity. This study also adds to the knowledge of brand management in marketing, specifically in the music industry.